High‐dose cyclophosphamide for hard‐to‐treat patients with relapsed or refractory B‐cell non‐Hodgkin's lymphoma, a phase II result. (28th January 2020) - Michot, Jean‐Marie; Annereau, Maxime; Danu, Alina; Legoupil, Clémence; Bertin, Louis; Chahine, Claude; Achab, Nadia; Antosikova, Anna; Cerutti, Ariane; Rossignol, Julien; Ghez, David; Willekens, Christophe; et al.
Abstract: Background: High‐dose cyclophosphamide to treat solid refractory tumors demonstrated meaningful activity, while data to treat lymphoma remain scarce. This study aims to assess high‐dose cyclophosphamide to treat relapsed or refractory lymphoma. Methods: A phase II study included adult patients with relapsed or refractory B‐cell non‐Hodgkin's lymphoma, previously treated by ≥2 prior lines with no other available option of therapy. High‐dose cyclophosphamide was given intravenously 3 g/m 2 over two consecutive days and repeated once at 28 days in responding patients. Rituximab 375 mg/m 2 intravenously was added in patients not refractory to anti‐CD20 antibody. Results: Forty‐two patients with median age 65 [56‐70] years were included. Patients had previously received a median of four lines of therapies. Tumor types were diffuse large B‐cell lymphoma (n = 26; 62%), indolent B‐cell non‐Hodgkin lymphoma (n = 10; 24%), or mantle lymphoma (n = 6; 14%). Hematologic and non‐hematologic grade 3‐5 toxicities occurred in 42 (100%) and 18 (43%) of patients, respectively. The overall response rate was 45%. Conclusion: One to two cycles of high‐dose cyclophosphamide in hard‐to‐treat patients with relapsed or refractory B‐cell non‐Hodgkin lymphoma demonstrated a favorable safety and efficacy profile. This regimen could serve as a bridge to modern cellular therapy with CAR‐T cell.